Effects of Polyphenol-Rich Foods on Chronic Diseases - de Pascual-Teresa, Sonia; Goya, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Polyphenols are a group of bioactive compounds in plant foods that have been gaining attention since the 1990s due to their health implications. However, it is still difficult to define their implications concerning health maintenance and chronic disease prevention or even treatment. There are many difficulties in their study, with the first being the fact that this group of compounds includes such a diverse array of chemical structures and effects as part of the food products in which they coexist with many other nutrients and non-nutrients. However, today, it is generally accepted that they exert a vasoprotective effect, that they may modulate blood pressure and exert a regulatory effect both on lipid and glucidic metabolism, and that they have an immunomodulatory and gut microbial effect. It is through all these means that polyphenols may be of use in the prevention and treatment of chronic diseases as prevalent as obesity and cardiovascular disease or neurocognitive decline.